2022
DOI: 10.1002/nop2.1170
|View full text |Cite
|
Sign up to set email alerts
|

Are nurses prepared to respond to next infectious disease outbreak: A narrative synthesis

Abstract: Over the past few decades, numerous communicable diseases have spread in human society, some of which have caused great threats, burdens and losses to human beings, such as the 2003 SARS epidemic (Stadler et al., 2003), the 2009 H1N1 influenza pandemic (Scalera & Mossad, 2009), the 2014 Ebola virus disease epidemic (Zawilińska & Kosz-Vnenchak, 2014), the 2015 MERS threat (Mackay & Arden, 2015) and the current outbreak of coronavirus disease (Valencia, 2020). These widespread infectious diseases represent one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…Psychological stress is also a serious issue among nurses, with the incidence of suicidal ideation reported to be between 3.6% and 8.4% during the COVID‐19 pandemic, and psychological support is particularly important (Smallwood et al, 2022 ). Different from other studies in which psychological issues were often ignored by superiors during the COVID‐19 pandemic (Nie et al, 2022 ), psychological support measures were mentioned by most administrators in this study, reflecting their attention to the psychological situation of employees. Interestingly, Marvel Comics teamed up with the Allegheny Health Network to create comics about nurses working tirelessly and courageously like heroes, to raise awareness of what nurses do during the pandemic and promote the role of nurses to younger audiences as an external factor that gives moral support to nurses worldwide (Marvel, 2020 ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Psychological stress is also a serious issue among nurses, with the incidence of suicidal ideation reported to be between 3.6% and 8.4% during the COVID‐19 pandemic, and psychological support is particularly important (Smallwood et al, 2022 ). Different from other studies in which psychological issues were often ignored by superiors during the COVID‐19 pandemic (Nie et al, 2022 ), psychological support measures were mentioned by most administrators in this study, reflecting their attention to the psychological situation of employees. Interestingly, Marvel Comics teamed up with the Allegheny Health Network to create comics about nurses working tirelessly and courageously like heroes, to raise awareness of what nurses do during the pandemic and promote the role of nurses to younger audiences as an external factor that gives moral support to nurses worldwide (Marvel, 2020 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Centralized leadership, efficient operation, and unified dispatch of the nursing management system are important for effective response to PHEs. Attitudes and intentions are direct factors influencing nurses' behaviour during the pandemic, which may be related to a safe working environment, adequate protective equipment, appropriate incentives and correct professional values, which are also in the scope of the 'structure' in this study (Nie et al, 2022). With limited information and unpredictable tasks, front-line nurses were suffering from great physical and psychological stress, and social stigma (Joo & Liu, 2021;Wahed et al, 2020), therefore, physical and psychological support from the perspective of organization were emphasized by most participants.…”
Section: Discussionmentioning
confidence: 98%
“…These differences can be explained by the fact that nurses’ perceptions of value, support and their needs may differ. For example, in a wider geographical area, nurses reported that their needs included adequate information as well as interpersonal and family needs [ 75 ]; others reported needing adequate training with psychological preparation [ 76 ]. In the present review, the need for nurses to be visible, recognised and appreciated and the demand for psychosocial support and resource management were the most prominent needs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Competent nursing practice was critically brought to the forefront during the COVID-19 pandemic [14,15]. This rare global pandemic led to the most intense scrutiny of nursing education and preparedness across multiple settings in recent history [16,17]. Nurses' experiences, knowledge, skills, and competency to handle this novel infectious disease have been important topics of discussion in the relevant literature [11,18].…”
Section: Introductionmentioning
confidence: 99%